Challenges for Islamic political parties in Indonesia : a case study of Partai Persatuan Pembangunan (PPP) - Amri, Marwah Fauziah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This thesis examines the challenges facing Islamic political parties in Indonesia focusing on United Development Party (PPP) as the case study. The thesis examines the various factors that contribute to weakening electoral support for Islamic political parties in Indonesia. Research indicates that the misconception of the priority of the Muslim voters, shifts in political orientations towards more pragmatic political attitudes, the politicization of religion and increased factionalism in Indonesian Islamic Parties are among the key factors shaping electoral trends and voters' behaviour towards Indonesian Islamic political parties. In response to declining public support, PPP has attempted to adjust its campaign platform towards more pragmatic positions with mixed outcomes.